The Impact of Virtual Reality Therapy in Managing Chronic Anxiety in Clinical Dipsychology - Zani, Benny Novico; Xu, Shanshan; Priyono, Dedit; Xavier, Murphy; Ajani, Anggra Trisna (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Many people around the world experience chronic anxiety, which is a mental health problem. This condition is characterized by excessive and ongoing worry, often for no apparent reason, which can interfere with daily life. Virtual reality (VR) therapy is one of the innovative approaches to treating mental health conditions in recent years thanks to advances in technology. This research was conducted with the aim of finding out, such as the realism of the virtual environment, interactivity, and length of exposure, some of the elements of virtual therapy that are most helpful in reducing anxiety. In addition, to identify topics that require additional research to increase empirical evidence on the effects of virtual reality therapy, as well as encourage long-term research to evaluate the long-term impact of virtual reality therapy on chronic anxiety. The method used by researchers in researching the Impact of Virtual Reality Therapy in Managing Chronic Anxiety in Clinical Psychology is to use a quantitative method. The data obtained by researchers was obtained from the results of distributing questionnaires. The distribution of questionnaires carried out by researchers was carried out online using Google From software. The results of data acquisition will also be tested again using the SPSS application. From the research results, it can be seen that studies have shown quite positive results regarding virtual reality (VR) therapy in the treatment of chronic anxiety. It is used as part of exposure therapy, where a person is gradually exposed to anxiety-inducing stimuli in a safe and controlled virtual environment. It is excellent for treating phobias, post-traumatic stress disorder (PTSD), and other anxieties. From this study, researchers can conclude that virtual reality (VR) therapy can be an effective treatment for anxiety. A person receiving VR therapy has the opportunity to confront and manage anxiety triggers in a controlled and safe environment, which helps them develop resilience and coping skills.